1994
DOI: 10.1002/bjs.1800810439
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized study of preoperative bowel cleansing for patients undergoing colorectal surgery

Abstract: Three different methods of preoperative bowel preparation were tested in a prospective randomized trial examining efficacy and morbidity. In all, 163 patients were treated by gut irrigation with Ringer's lactate, Prepacol or polyethylene glycol (PEG). Fluid retention, cleansing effect, postoperative complications and subjective acceptance were documented. Relevant weight gain and decrease in haematocrit indicating fluid retention were seen only after the use of Ringer's lactate. There were no significant diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…52 Previous studies have shown that a vigorous 72-h mechanical cleansing regimen only produced a significant reduction in coliforms, while the residual colonic microflora remained unchanged. [52][53][54] In unprepared colon, besides the possibility of wound infections, the bacteria can also lead to local infection of the anastomosis, causing leakage. 55,56 In our study, we found higher frequency of E. coli, Klebsiella, Pseudomonas species, and Bacteroides in patients with anastomotic leakage after low anterior resection.…”
Section: Discussionmentioning
confidence: 99%
“…52 Previous studies have shown that a vigorous 72-h mechanical cleansing regimen only produced a significant reduction in coliforms, while the residual colonic microflora remained unchanged. [52][53][54] In unprepared colon, besides the possibility of wound infections, the bacteria can also lead to local infection of the anastomosis, causing leakage. 55,56 In our study, we found higher frequency of E. coli, Klebsiella, Pseudomonas species, and Bacteroides in patients with anastomotic leakage after low anterior resection.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 However, current methods of mechanical bowel preparation rarely provide a completely "clean" bowel, but instead often result in fluid bowel contents. Although previous studies have not definitively proven that intraoperative spillage of bowel contents accounts for these infectious complications, this may be one potential explanation.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] The rigid regimen of wholebowel irrigation has nowadays been replaced by less discomforting methods of bowel preparation, mainly by the use of agents that act as osmotic and contact laxatives, such as polyethylene glycol (PEG), sodium picosulfate, and sodium phosphate. Previous studies demonstrate that these agents can induce osmotic disturbances in the elderly and may prolong hospital stay.…”
Section: Originalmentioning
confidence: 99%